Comparison of stigmatizing views towards COVID-19 and mental disorders among adolescent and young adult students in China - Zhang, Tian-Ming; Zhang, Xin-Feng; Meng, Xian-Dong; Huang, Yi; Zhang, Wei; Gong, Hui-Hui; Chan, Sherry Kit Wa; Chen, Xiao-Chuan; Gao, Ru; Lewis-Fernández, Roberto; Fan, Yuan-Yuan; Liu, Chang-Cheng; et al. (Frontiers in Psychiatry, 2023)
Objective: Infectious diseases including COVID-19 and mental illness are two of the most common health conditions associated with stigma. However, the comparative stigma of these two conditions has received little attention in research. This study aimed to compare the prevalence of stigmatizing views towards people with COVID-19 and mental illness, and the factors associated with these views, among a large sample of adolescent and young adult students in China. Methods: A total of 9749 youth aged 15-24 years old completed a survey on stigmatizing attitudes towards COVID-19 and mental illness, as well as mental health-related factors, including general mental health status and symptoms of depression, anxiety, insomnia, and posttraumatic stress disorder (PTSD). Multivariable linear regression analyses were conducted to identify factors associated with stigmatizing views. Findings: Prevalence of COVID-19 and mental illness-related stigma were 17.2% and 40.7%, respectively. COVID-19-related stigma scores were significantly higher among males (β=0.025, p<0.05), without quarantine experience (β=0.035, p<0.001), and with lower educational level (p<0.001), lower family income (p<0.01), and higher PTSD symptoms (β=0.045, p<0.05). Mental illness-related stigma scores were significantly higher among individuals with average and lower-than-average levels of family income (p<0.01), with depression symptoms (β=0.056, p<0.001), anxiety symptoms (β=0.051, p<0.001), and mental health problems (β=0.027, p<0.05). Conclusion: The stigma of mental illness is higher in youth population than the stigma of COVID-19. Factors associated with stigmatizing attitudes towards people with COVID-19 and mental illness varied across the youth. Stigma-reduction interventions among youth should be targeted specifically to COVID-19 or mental illness conditions.